(untitled) (Journal of Social Economics Research, 2019)
Many households in Ghana experience high poverty levels and unreliable sources of income. As a strategy to reduce poverty level in Ghana, there are various decisions by individuals within the household to either migrate internally or engage in other activities that generate income. This study examines the use of internal migration as a livelihood strategy in Ghana using descriptive statistics and logit regression with data from the 2012/2013 Ghana Living Standards Survey (GLSS 6). In relation to most previous empirical studies, this study provides results consistent with the economic reasons for migration in Ghana. The probit regression estimates and the use of descriptive statistics support the diversification framework of livelihoods–where some internal migrants in Ghana take up multiple jobs as a means of obtaining multiple incomes. According to the findings, most migrants end up in the private informal sector at their destination places. Finally, in terms of regional distribution of internal migrants, households from the three northern regions are more likely to migrate. It is recommended that development policies of the government should be evenly distributed to ensure national development, irrespective of where one finds one’s self. Education should also be promoted to ensure that migrants have some form of learning in order to obtain employment in either the semi-formal or formal sector which requires a high level of skills.